Modular metabolic engineering for production of phloretic acid, phloretin and phlorizin in Escherichia coli. (16th January 2022) - Liu, Xue; Liu, Jincong; Lei, Dengwei; Zhao, Guang-Rong
Highlights: Engineered E. coli produced highest titer of phloretic acid from glucose. A novel functional 4CL facilitated the biosynthesis of phloretin in E. coli . Structure-guiding mutagenesis of MdCHS3 increased the production of phloretin. Phloretin was effieciently bioconverted to phlorizin. Abstract: Phloretic acid, phloretin and phlorizin (phloretin 2′-O-glucoside), plant-derived natural products, are well known for human health benefits and medical application. Here, we construct an artificial biosynthetic pathway of phlorizin by modular engineering strategy and realize the production of phloretic acid, phloretin and phlorizin in Escherichia coli . Extending from L-tyrosine biosynthetic pathway, we firstly established the phloretic acid module comprised of heterologous TAL and ER enzymes, and highest titer of phloretic acid was achieved from glucose. Then, through biochemical screening of functional microbial Aa4CL and structure-based mutagenesis of MdCHS3 in phloretin module, we successfully constructed the phloretin biosynthetic pathway. Finally, we tested several glycosyltransferases in phlorizin module, and phloretic acid was bioconverted to phlorizin. This is the first report on biosynthesis of phloretin and phlorizin in engineered E. coli, indicating the promising potential of microbial cell factories to produce natural and unnatural dihydrochalcones.